Análisis preliminar de las concepciones de estudiantes ingresantes sobre actitudes y valores ético-morales de la profesionalidad veterinaria - Alzola, Paula (Universidad Nacional del Litoral, 2022)
The teaching of professionalism and the construction of professionalism is one of the axes of the new curricular designs in careers of human and veterinary medicine at an international level. The objective of this work was to investigate the assessment of the incoming students at the Faculty of Veterinary Sciences of the National University of the Center of the Province of Buenos Aires in relation to attitudes and ethical-moral values ​​specific to veterinary medical professionalism. A survey with a Lickert-type scale was administered to 80 students. Most of the students placed in high values ​​of importance the general principles of ethics, attitudes and values ​​towards the clients, the animals, the work and towards themselves of the veterinary professionals. The results would indicate the presence of an important cognitive base that would allow to include explicitly the work with capacities, abilities and professional values ​​in the study plans from the moment of admission.